Anda di halaman 1dari 24

# MH1100/MTH112: Calculus I.

## Solutions to the Week #2 problem set.

Solution to Problem 1.
In this problem we are asked to guess the slope of the tangent to the graph
x
at the point P (1, 12 ) by looking at the slopes of
of the function f (x) = 1+x
various secants starting at that point.
Consider, for example, the rst case we are asked to use: the secant from
P (1, 0.5) to Q(0.5, f (0.5)). Here is a graph of that secant:
0.6

0.5

0.4

0.3

0.2

0.1

0.1

0.2

0.2

0.4

0.6

0.8

1.2

m0.5 =

0.5
0.5 1+0.5
0.5 f (0.5)
=
= 0.333.
1 0.5
1 0.5

## The other slopes we are asked for are:

0.5 1+0.9
0.5 f (0.9)
=
= 0.263
1 0.9
1 0.9
0.99
0.5 1+0.99
0.5 f (0.99)
=
= 0.251
1 0.99
1 0.99
0.999
0.5 1+0.999
0.5 f (0.999)
=
= 0.250
1 0.999
1 0.999
1.5
f (1.5) 0.5
1+1.5 0.5
=
= 0.2
1.5 1
1.5 1
1.1
0.5
f (1.1) 0.5
= 1+1.1
= 0.238
1.1 1
1.1 1
1.01
0.5
f (1.01) 0.5
= 1+1.01
= 0.248
1.01 1
1.1 1
1.001
f (1.001) 0.5
1+1.001 0.5
=
= 0.2499
1.001 1
1.001 1
0.9

m0.9 =
m0.99 =
m0.999 =
m1.5 =
m1.1 =
m1.01 =
m1.001 =

Considering these slopes, we can say that the slopes seem to be approaching the value 0.25 as x approaches 1 from the left and also from the right.
So our guess for the slope of the tangent to the graph of f (x) at x = 1 is
0.25.
The tangent, then, is the straight line going through the point (1, 0.5)
with gradient 0.25. That line is given by the equation:
0.25 =

y 0.5
.
x1

In other words:

1
1
y = x+ .
4
4
Here is a plot of that tangent, which suggests that our guess is a good

approximation:

0.9
0.8
0.7
0.6
0.5
0.4
0.3
0.2
0.1
0
0.1

0.5

1.5


Problem 2: (Problem 1.4.5 in [Stewart].)
If a ball is thrown into the air with a velocity of 10m/s, its height in metres
t seconds later is given by H(t) = 10t 4.9t2 .
(a) Find the average velocity for the time beginning when t = 1.5 and
lasting
(i)
(iii)

0.5 seconds
0.05 seconds

(ii)
(iv)

0.1 seconds
0.01 seconds.

## (b) Estimate the instantaneous velocity when t = 1.5.

Solution
To begin, we are asked for the average velocity that the ball has in the
1
2 second period after t = 1.5. To determine that, we divide the distance
covered by the ball in that period by the length of the time period. We

obtain:
Distance travelled by the ball between t = 1.5 and t = 1.5 + 0.5 = 2
,
Half a second
H(2) H(1.5)
=
,
(0.5)
(10 (2) 4.9 (2)2 ) (10 (1.5) 4.9 (1.5)2 )
=
,
0.5
= 7.15 m sec1 .
(The case t = 0.1). The average velocity the ball has in the 0.1 second
period after t = 1.5 is:
Distance travelled by the ball between t = 1.5 and t = 1.6
,
0.1
H(1.6) H(1.5)
=
,
0.1
(10 (1.6) 4.9 (1.6)2 ) (10 (1.5) 4.9 (1.5)2 )
,
=
0.1
= 5.19 m sec1 .
(The case t = 0.05). The average velocity the ball has in the 0.05 second
period after t = 1.5 is:
Distance travelled by the ball between t = 1.5 and t = 1.55
,
0.05
H(1.55) H(1.5)
=
,
0.05
(10 (1.55) 4.9 (1.55)2 ) (10 (1.5) 4.9 (1.5)2 )
=
,
0.05
= 4.945 m sec1 .
(The case t = 0.01). The average velocity the ball has in the 0.01 second
period after t = 1.5 is:
Distance travelled by the ball between t = 1.5 and t = 1.51
,
0.01
H(1.51) H(1.5)
=
,
0.01
(10 (1.51) 4.9 (1.51)2 ) (10 (1.5) 4.9 (1.5)2 )
=
,
0.01
= 4.749 m sec1 .
4

## In part (b), we are asked to estimate the instantaneous velocity when

t = 1.5. Our calculations in Part(a) might lead us to estimate 4.7 metres
per second, because that seems to be what our result is approaching, as t
approaches zero. (Of course, this is only a guess!)

Problem 3: (Problem 1.5.6 in [Stewart].)
We were given the graph of some function h(x), and are asked to determine
a number of quantities, or explain why they do not exist. We nd:
(a) limx3 h(x) = 4.
(b) limx3+ h(x) = 4.
(c) limx3 h(x) = 4. Comment: The two 1-sided limits exist and are
equal, so the limit exists, even though the function is dened by two
dierent rules on the two sides of 3, and h(x) is not even dened at
that point.
(d) h(3) does not exist. 3 is not in the domain of h(x).
(e) limx0 h(x) = 1.
(f) limx0+ h(x) = 1.
(g) limx0 h(x) does not exist. Comment: The two 1-sided limits both
exist, but are dierent, so this limit does not exist.
(h) h(0) = 1.
(i) limx2 h(x) = 2.
(j) h(2) does not exist. Comment: again, note that even though the
function is not dened at 2, the limit at that point exists.
(k) limx5+ h(x) = 3.
(l) limx5 h(x) does not exist. Comment: As we approach 5 from the
left, the function does not seem to approach any particular value. It
just keeps oscillating.


## Problem 4: (Problem 1.5.16 in [Stewart])

Give an example of a function f satisfying the following conditions:
limx0 f (x) = 1, limx0+ f (x) = 1, limx2 f (x) = 0, limx2+ f (x) = 1,
f (2) = 1, and f (0) is undened.
Solution
This is an example of a problem which can be solved in many, in fact,
countless, dierent ways. For example, here is one solution:
3
2.5
2
1.5
1
0.5
0
0.5
1
1.5
2
1

0.5

0.5

1.5

2.5

3
2.5
2
1.5
1
0.5
0
0.5
1
1.5
2
1

0.5

0.5

1.5

2.5

## Solution to Problem 5: (Problem 1.5.19 in [Stewart])

This problem asks us to guess the limit:
x2 2x
x2 x2 x 2
lim

## by evaluating the function f (x) =

points. If we do that:
x
2.5
2.1
2.05
2.01
2.005
2.001
1.9
1.95
1.99
1.995
1.999

x2 2x
x2 x2

f (x)
0.7143
0.6774
0.6721
0.6678
0.6672
0.6668
0.6552
0.6610
0.6656
0.6661
0.6666

## These values lead us to guess that the limit is equal to:

x2 2x
2
.
2
x2 x x 2
3
lim

(Note that it is also straightforward to prove this exactly using the limit
laws and a simple rearrangement:
x(x 2)
x
2
x2 2x
= lim
= lim
= ,
2
x2 x x 2
x2 (x 2)(x + 1)
x2 x + 1
3
lim

as required.)


## Problem 6: (Problem 1.6.2 in [Stewart])

We are given the graphs for two functions, f and g, and are asked to investigate a number of related quantities.
(a) First we are asked for limx2 (f (x)+g(x)). Well, notice that the limits
of the pieces exist:
limx2 f (x) = 2,
limx2 g(x) = 0.
It thus follows from the Limit law for sums that the sum (f (x)+g(x))
also has a limit at x = 2, and it is equal to:
lim (f (x) + g(x)) = lim f (x) + lim g(x) = 2.

x2

x2

x2

(b) The limit limx1 (f (x) + g(x)) does not exist. This is because:
lim (f (x) + g(x)) = lim (f (x)) + lim (g(x)) = 1 + 2 = 3,

x1

x1

x1

while
lim (f (x) + g(x)) = lim (f (x)) + lim (g(x)) = 1 + 1 = 2.

x1+

x1+

x1+

Because the 1-sided limits are dierent, this limit doesnt exist.
(c) We are asked to evaluate limx0 (f (x)g(x)). Because:
limx0 f (x) exists and equals 0, and:
limx0 g(x) exists and is approximately equal to 1.4
it follows that
lim (f (x)g(x)) = lim (f (x)) lim (g(x)) 0 1.4 = 0.

x0

x0

x0

(d) Notice that we cannot apply the Limit law for quotients to this
function because
lim g(x) = 0.
x1

Actually:
lim

f (x)
=
g(x)

lim

f (x)
= .
g(x)

x1+

while
x1

(
)
(e) We are asked to evaluate limx2 x3 f (x) , if it exists. Well, to begin,
note that:
limx2 x3 exists and is equal to 8.
limx2 f (x) also exists (looking at the graph), and is equal to 2.
Thus, because the pieces have limits, we can apply the Limit law for
products and write:
)
)(
(
) (
lim x3 f (x) = lim x3
lim f (x) = 8 2 = 16.
x2

x2

x2

## (f) We are asked to evaluate limx1 3 + f (x). To begin, notice that,

because of various simple limit laws, the piece inside the square root
has a limit:
lim (3 + f (x)) exists and is equal to 4.

x1

## lim 3 + f (x) = lim (3 + f (x)) = 4 = 2.

x1

x1

Problem 7:
Use the limit laws to evaluate the limit
(
)3
1 + 3x
lim
,
x1 1 + 4x2 + 3x4
carefully justifying each step.
Solution
1. To begin, note that limx1 (1 + 3x) exists and is equal to 4 (by the
limit laws for simple functions and for sums).
2. Furthermore, note that limx1 (1 + 4x2 + 3x4 ) exists and is equal to:
=
=
=
=

## limx1 (1 + 4x2 + 3x4 )

limx1 (1) + limx1 (4x2 ) + limx1 (3x4 )
(Limit law for sums.)
2
4
limx1 (1) + 4 (limx1 x) + 3 (limx1 x) (Limit law for products.)
1+4+3
(Simple functions.)
8.

3. Then, because:
limx1 (1 + 3x) exists, and:
limx1 (1 + 4x2 + 3x4 ) exists, and is not equal to zero,
it follows from the Limit law for quotients that:
4
1
1 + 3x
limx1 (1 + 3x)
= = .
=
2
4
2
4
x1 1 + 4x + 3x
limx1 (1 + 4x + 3x )
8
2
lim

(
lim

x1

1 + 3x
1 + 4x2 + 3x4

)3

(
=

1 + 3x
x1 1 + 4x2 + 3x4
lim

)3
=

( )3
1
1
= .
2
8


10

## Problem 8: (1.6.10 in [Stewart])

(a) What is wrong with the following equation?
x2 + x 6
=x+3
x2
(b) Given your answer to (a), explain why the following equation is correct.
x2 + x 6
= lim (x + 3).
x2
x2
x2
lim

Explanation
The equation:

x2 + x 6
=x+3
x2

## is incomplete because the domain of the left-hand side is equal to R\{2},

while the domain of the right-hand side is R. (In other words, the left-hand
side does not give any value when evaluated at x = 2.)
But the equation:
x2 + x 6
= lim (x + 3)
x2
x2
x2
lim

is nevertheless correct, because the limit of a function, limxa f (x), does not
depend on the denition of f (x) at x = a. Looking at the above equation,
we observe that:
x2 + x 6
(x 2)(x + 3)
=
=x+3
x2
(x 2)
everywhere except the point that we are taking the limit.


11

## Problem 9: (1.6.15 from [Stewart])

Evaluate the following limit, if it exists:
lim

t3

t2 9
.
2t2 + 7t + 3

Solution
In this problem, and many similar problems to follow, we will skip some of
the detail that accompanies the use of the limit laws. (That is, to give a
completely precise proof of the fact below we would note, at each step, that
the appropriate assumptions of the appropriate limit law were met. But
the following problem is just looking for an algebraic trick, which we will
describe. In an exam situation, it will made be quite clear what level of
detail to use.)
t2 9
t3 2t2 + 7t + 3
lim

(t 3)(t + 3)
(2t + 1)(t + 3)
(t 3)
= lim
t3 (2t + 1)
6
=
.
5
=

lim

t3


Solution to Problem 10:

1+h1
lim
h0
h

=
=
=
=

1+h1
1+h+1
lim

h0
h
1+h+1
(
)2
2
1+h 1
)
lim (
h0 h
1+h+1
1
lim
h0
1+h+1
1
.
2


12

## Solution to Problem 11:

x+23
lim
x7
x7

x+23
x+2+3
= lim

x7
x7
x+2+3
(x 7)

= lim
x7 (x 7)( x + 2 + 3)
1
=
.
6


lim

1
4

x4

+ x1
4+x

lim

4+x
4x

4+x
1
= lim
x4 4x
1
.
=
16
x4

## Solution to Problem 13:

x2 81
lim
x9
x3

(x 9)(x + 9)

x3

( x 3)( x + 3)(x + 9)

= lim
x9
x3
= 108.
=

lim

x9

13

## Solution to Problem 14: (1.6.29 from [Stewart])

(
lim

t0

1
1

t
t 1+t

)
11 1+t

lim
t0 t
1+t

(
)
1 (1 1 + t) (1 + 1 + t)

lim
t0 t
1 + t (1 + 1 + t)
1
(t)

lim
t0 t (1 + 1 + t) 1 + t
1

lim
t0 (1 + 1 + t) 1 + t
1
.
2
(

)
=
=
=
=
=

## Problem 15: (1.6.36 from [Stewart])

Use the squeeze theorem to show that

lim x3 + x2 sin = 0.
x0
x
Solution
Well prove this limit by applying the squeeze theorem with a choice of:

g1 (x) = x3 + x2 , and

g2 (x) = x3 + x2 .
To begin, note that:

x3 + x2 sin x3 + x2 sin x3 + x2 sin x3 + x2 .
x
x
x
Similarly:

x3 + x2 sin x3 + x2 sin x3 + x2 sin x3 + x2 .
x
x
x
Thus, we have shown that:

x3 + x2 x3 + x2 sin x3 + x2 .
x
Next, observe that (using elementary limit laws):
lim g1 (x) = lim g2 (x) = 0.

x0

x0

## It now follows from the squeeze theorem that:

14

The limit limx0 x3 + x2 sin x exists, and that

limx0 x3 + x2 sin x = 0.
Here is a plot of the three functions involved in the proof:
1.5

0.5

0.5

1.5
1.5

0.5

0.5

1.5

## The top graph

(in black) is g2 (x) = x2 + x3 . The middle graph(in blue)

## is f (x) = x2 + x3 sin( x ). The lower graph (in red) is g1 (x) = x2 + x3 .


Problem 16: (1.6.40 from [Stewart])
Prove that
lim

x0+

x 1 + sin

2
x

)]
= 0.

Solution
Well prove this with a 1-sided squeeze theorem, with a choice of:
g1 (x) = 0

g2 (x) = 2 x.
Well start by establishing that
[
( )]

2 2
g1 (x) x 1 + sin
g2 (x)
x
15

## when x > 0, as required by the assumptions of the squeeze theorem.

We begin with the following, which follows from the basic properties of
the function sin x:
0 sin2 (2/x) 1.
Adding 1 to this we get:
1 1 + sin2 (2/x) 1 + 1 = 2.

## Multiplying this through by x, we deduce:

0 x x [1 + sin2 (2/x)] 2 x,
as required.

## Furthermore, observe that: limx0+ 0 = 0, and limx0+ 2 x = 0. Thus

all the assumptions of the squeeze theorem are satised for these choices of
g1 and g2 . It then follows that:

## limx0+ x [1 + sin2 (2/x)] = 0.

Here is the picture. The top graph is of 2 x, and the one under it is

of x(1 + sin2 (2/x)). Note that we could equally well have squeezed our

3
2.5
2
1.5
1
0.5
0
0.5
1
1

0.5

0.5

1.5

2.5


16

## Problem 17: (1.6.41 from [Stewart])

Does the following limit exist? If so, determine the limit. If not, explain
why not.
lim (2x + |x 3|) .
x3

Solution
The clearest way to understand this problem is to study the 1-sided limits
of the function at x = 3. Observe that:
lim (2x + |x 3|) =

x3+

lim (2x + x 3)

x3+

= (9 3),
= 6.
(We have obtained the rst equality by using the fact that |x 3| = (x 3)
when x 3.)
Furthermore:
lim (2x + |x 3|) =

x3

## lim (2x (x 3))

x3

= 3 + 3,
= 6.
Because the two 1-sided limits exist, and are equal, it follows that
lim (2x + |x 3|) = 6.

x3

17

## Problem 18: (1.6.45 and 1.6.46 from [Stewart])

Do the following limits exist? If so, determine the limits.
(
)
1
(i) limx0 x1 |x|
(
(ii) limx0+

1
x

1
|x|

## Solution to Part (i)

We are studying the left-hand limit at x = 0. Thus we are interested in the
1
values that the function x1 |x|
takes on negative values of x. Note that
when x 0, |x| = x. Thus:
)
)
(
(
1
1
1
1

= lim
+
lim
|x|
x
x0 x
x0 x
2
= lim
x0 x
= .
Solution to Part (ii).
In this case, we are studying the right-hand limit at x = 0. Note that when
x 0, |x| = x. Thus:
)
(
)
(
1
1
1
1

= lim

lim
|x|
x
x0+ x
x0+ x
= lim 0
x0+

= 0.


18

Problem 19:
Consider the function
F (x) =

x2 1
.
|x 1|

## (i) Find limx1+ F (x).

(ii) Find limx1 F (x).
(iii) Does limx1 F (x) exist?
(iv) Sketch the graph of F (x).
Solution
To understand this function, we should rst carefully state the rule that
determines the function in the dierent regions. Note rst that the domain
of the function is R\ {1}. Also note that when x > 1, x 1 > 0, so
|x 1| = x 1. And when x < 1, x 1 < 0, so |x 1| = (x 1).
Thus:
{ 2
x 1
when x > 1,
x1
F (x) =
2
x 1
when x < 1.
1x
{
(x + 1) when x > 1,
=
(x + 1) when x < 1.
With this formula it is clear that:
lim F (x) = 2 while

x1+

lim F (x) = 2.

x1

So, because the two 1-sided limits are dierent, the limit limx1 F (x) does
not exist.

19

## Here is the graph of this function:

4
3
2
1
0
1
2
3
4
3


Problem 20: (1.6.55 from [Stewart])
If p(x) is a polynomial, show that limxa p(x) = p(a).
Solution
If p(x) is a polynomial, that means that it is of the form:
c0 + c1 x + c2 x2 + . . . + cn xn
for some numbers c0 , c1 , . . . , cn . The deduction of the required formula now
proceeds in the following way:
=
=
=
=
=

limxa p(x)
(
)
limxa c0 + c1 x + c2 x2 + . . . + cn xn (
)
limxa (c0 ) + limxa (c1 x) + limxa c2 x2 + . . . + limxa (cn xn )
c0 + c1 limxa x + c2 (limxa x)2 + . . . + cn (limxa x)n
c0 + c1 a + c2 a2 + . . . cn an
p(a).

## It is possible to compress this theorem by using -notation, where we

would write:
n

2
n
p(x) = c0 + c1 x + c2 x + . . . + cn x =
ci xi .
i=1

20

## With this notation the deduction becomes:

( n
)
i
limxa p(x) = lim
i=0(ci x )
nxa
=
limxa ci xi (By the limit law for sums.)
ni=0
i
=
(By the limit law for products
i=0 ci (limxa x)
and simple functions.)
n
i
=
(Because limxa x = a.)
i=0 ci a
= p(a).

Problem 21: (1.6.56 from [Stewart])
If r(x) is a rational function (recall that this means that r(x) = p(x)
q(x) for
some polynomials p(x) and q(x)), show that limxa r(x) = r(a) for every
number in the domain of r(x).
Solution
If r(x) is a rational function, that means that it is of the form p(x)
q(x) for two
polynomials p(x) and q(x). The domain of r(x) is precisely the set of points
a where q(a) = 0. For such points, it follows from the Quotient law for
limits that:
limxa p(x)
p(a)
p(x)
=
=
,
lim
xa q(x)
limxa q(x)
q(a)
(where the last equality above was the result of the previous exercise on the
limits of polynomials).
Thus:
p(a)
p(x)
=
= r(a).
lim
xa q(x)
q(a)


21

If limx1
carefully.

f (x)8
x1

## = 10, then what is limx1 f (x)? Explain your deduction

Solution
The trick here is to arrange the expression f (x) so that
( we )can use the
information we have, which is that the limit limx1 f (x)8
exists and
x1
equals 10. To use this information we write:
f (x) =

f (x) 8
(x 1) + 8.
x1

## Now we can build up the deduction carefully.

)
(
and limx1 (x 1)
1. To begin, note that the limits limx1 f (x)8
x1
both exist (by assumption and by a simple
calculation),
(
) so, by the
f (x)8
limit law for products, the limit limx1 x1 (x 1) also exists,
and equals
(
)
(
)
f (x) 8
f (x) 8
lim
(x 1) = lim
lim (x 1) = 10 0 = 0.
x1
x1
x1
x1
x1
(

f (x)8
x1

## 2. Now observe that because both of the limits limx1

(x 1)
and limx1 8 exist, then, by the limit law for sums, we can deduce that
the limit
(
)
f (x) 8
lim f (x) = lim
(x 1) + 8
x1
x1
x1
also exists and equals
(
)
f (x) 8
(x 1) + lim 8 = 0 + 8 = 8.
lim
x1
x1
x1
So limx1 f (x) = 8.

22

## () Problem 23: (1.6.59 from [Stewart])

Consider the function
{
f (x) =

x2
0

if x is rational
.
if x is irrational

## Prove that limx0 f (x) = 0.

Solution
This is going to be a direct application of the squeeze theorem. The functions
we will squeeze this function between are:
g1 (x) = 0,
g2 (x) = x2 .
Clearly,
lim g1 (x) = lim g2 (x) = 0

x0

x0

## so the only thing we need to explain is why

g1 (x) f (x) g2 (x).
The clearest way to explain this fact logically is to separately check the
two cases: the case where x is rational and the case where x is irrational.
If x is rational then f (x) = x2 , and the inequality we have to check is
0 x2 x2 ,
which is clearly true.
On the other hand, if x is irrational, then the equality that needs to be
checked is
0 0 x2 ,
which, again, is clearly true.
Thus the assumptions of the squeeze theorem are satised, and we can
now deduce that
lim f (x) = 0.
x0

23

## () Problem 24: (1.6.61 from [Stewart])

Find an example to illustrate the fact that it is possible for limxa (f (x)g(x))
to exist even though neither limxa f (x) nor limxa g(x) exists.
Solution
There are countless correct solutions here. How about setting a = 0 and
{
1
if x < 0,
f (x) = g(x) =
if x 0.
1


24